5. Albumin and Globulin Levels of Sumatran Elephants’ (Elephas maximus sumatranus) Blood at Elephant Conservation Center of Saree, Aceh Besar - Abdul Rahman; Al- Azhar; Rusli Rusli; Muhammad Isa; Arman Sayuti; Roslizawaty Roslizawaty (Universitas Syiah Kuala, 2018)
This research was done to determine albumin and globulin levels of Sumatran elephants’ blood at the Elephant Conservation Center (ECC) of Saree, Aceh Besar. In this study blood samples were collected from 6 Sumatran elephants at the ECC. The levels of albumin and globulin were determined spectrophotometrically. The data obtained were analyzed by t-test. The results showed that the average levels of albumin and the globulin of Sumatran elephants were 4, 25±0, 31 g/dL and 2, 33±0, 62 g/dL. Blood albumin and globulin levels of male Sumatran elephants were 4.23±0.05 g/dL and 2.36±0.77 g/dL, respectively; and those of female Sumatran elephants were 4.16±0.49 g/dL and 2.30±0.60 g/dL, respectively. The results of data analysis using t-test showed that blood levels of albumin or globulin of male and female Sumatran elephants were not significantly different (P 0.05). In conclusion, in the Sumatran elephants, blood albumin and globulin levels were not influenced by sex.